Climate change hazards along the Indian coastal districts: spatial analysis on a climatic impact-driver framework - Gills, Reshma; Padua, Shelton; Ramachandran, C.; Ratheesh, K.R.; Varghese, Eldho (Current Science, 2024)
Concepts, approaches and frameworks for assessing the impacts of climate change are evolving quickly. Due to their particular geographic location, proximity to oceans, concentration of populated regions, and infrastructure, coastal communities are particularly sensitive to the effects of climate change. The present study aims to develop a thematic map based on the CID (climatic impact-drivers) framework proposed in the assessment report-6 of the Intergovernmental Panel on Climate Change (IPCC) to evaluate the climate change's physical hazards in the coastal districts of India. The study points out that West Bengal and Odisha are the two states with the highest cyclone hazard index values making them most vulnerable to cyclones. At the same time, Kerala, Andhra Pradesh and West Bengal respectively fall in the extremely severe category of flood, heatwave and shoreline change hazards. The maritime state of Gujarat along with Diu and Daman experiences maximum severity for the sea level rise hazard. The multi-hazards index developed in the study by considering 14 threshold-based CID indices showed that the coastal state of Andhra Pradesh has the highest proneness to the physical hazards due to climate change.
Keywords: Flood; Heatwave; Multi-Hazard; Shoreline Change; Cyclone